Sobre una antiga composició lírica de la Romània: versions, temes, motius i formes - Romeu i Figueras, Josep (Caplletra. Revista Internacional de Filologia, 2004)
The author looks at an ancient poem from the romance language domain, fromits first documented appearances, which starts with «Eu·m levei un bon matí» orsimilar words and goes on to explore the thematic motif of the nightingale as aconfidant and messenger on romantic errands.